I don't know what table you have as reference, but I suspect it includes the following transforms:
[tex]1 \leftrightarrow \dfrac1s[/tex]
[tex]e^{at} \leftrightarrow \dfrac{1}{s-a}[/tex]
[tex]\cos(at) \leftrightarrow \dfrac{s}{s^2+a^2}[/tex]
[tex]\sin(at) \leftrightarrow \dfrac{a}{s^2+a^2}[/tex]
[tex]\cosh(at) \leftrigharrow \dfrac{s}{s^2-a^2}[/tex]
[tex]\sinh(at) \leftrigharrow \dfrac{a}{s^2-a^2}[/tex]
It probably also includes some more general properties, like
[tex]t f(t) \leftrightarrow -F'(s)[/tex]
[tex]e^{at} f(t) \leftrightarrow F(s-a)[/tex]
where F(s) is the Laplace transform of f(t).
Beyond these, you should also know the following identities:
[tex]\cosh(t) = \dfrac{e^t + e^{-t}}2[/tex]
[tex]\cosh^2(t) = \dfrac{1 + \cosh(2t)}2[/tex]
[tex]\cos^2(t) = \dfrac{1 + \cos(2t)}2[/tex]
[tex]\sin^2(t) = \dfrac{1 - \cos(2t)}2[/tex]
[tex]\sin(2t) = 2 \sin(t) \cos(t)[/tex]
[tex]\sin(t \pm T) = \sin(t) \cos(T) \pm \cos(t) \sin(T)[/tex]
Putting everything together, we have
• (a)
[tex]\cosh(t) \sin(t) = \dfrac{e^t + e^{-t}}2 \times \sin(t) = \dfrac12 e^t \sin(t) + \dfrac12 e^{-t} \sin(t)[/tex]
and the Laplace transform is
[tex]\dfrac12 F(s - 1) + \dfrac12 F(s + 1)[/tex]
where F(s) is the transform of sin(t),
[tex]F(s) = \dfrac{1}{s^2 + 1}[/tex]
Then
[tex]\cosh(t) \sin(t) \leftrightarrow \dfrac{\frac1{(s-1)^2+1} + \frac1{(s+1)^2+1}}2 = \boxed{\dfrac{s^2+2}{s^4+4}}[/tex]
• (b)
[tex]\sin^2(t) = \dfrac12 \left(1 - \cos(2t)\right)[/tex]
and the transform is
[tex]F(s) = \dfrac12 \left(\dfrac1s - \dfrac{s}{s^2+4}\right) = \boxed{\dfrac{2}{s^3+4s}}[/tex]
• (c)
[tex]\cos^2(2t) = \dfrac12 \left(1 + \cos(4t)\right)[/tex]
with transform
[tex]F(s) = \dfrac12 \left(\dfrac1s + \dfrac{s}{s^2+16}\right) = \boxed{\dfrac{s^2+8}{s^3+16s}}[/tex]
• (d)
[tex]\cosh^2(t) = \dfrac12 \left(1 + \cosh(2t)\right)[/tex]
with transform
[tex]F(s) = \dfrac12 \left(\dfrac1s + \dfrac{s}{s^2-4}\right) = \boxed{-\dfrac2{s^3-4s}}[/tex]
• (e)
[tex]t\sinh(2t) \leftrightarrow -F'(s)[/tex]
where F(s) is the Laplace transform of sinh(2t),
[tex]F(s) = \dfrac{2}{s^2 - 4} \implies -F'(s) = \boxed{\dfrac{4s}{(s^2-4)^2}}[/tex]
• (f)
[tex]\sin(t) \cos(t) = \dfrac12 \left(2\sin(t) \cos(t)\right) = \dfrac12 \sin(2t)[/tex]
with transform
[tex]F(s) = \dfrac12 \times \dfrac{2}{s^2+4} = \boxed{\dfrac1{s^2+4}}[/tex]
• (g)
[tex]\sin\left(t+\dfrac\pi4\right) = \sin(t) \cos\left(\dfrac\pi4\right) + \cos(t) \sin\left(\dfrac\pi4\right) = \dfrac1{\sqrt2} \left(\sin(t) + \cos(t)\right)[/tex]
with transform
[tex]F(s) = \dfrac1{\sqrt2} \left(\dfrac1{s^2+1} + \dfrac{s}{s^2+1}\right) = \boxed{\dfrac{s+1}{\sqrt2 (s^2+1)}}[/tex]
The last two are trivial and follow directly from the properties listed above.
• (h)
[tex]\cos(2t) - \cos(3t) \leftrightarrow \dfrac{s}{s^2+4} - \dfrac{s}{s^2+9} = \boxed{\dfrac{5s}{s^4 + 13s^2 + 36}}[/tex]
• (i)
[tex]\sin(2t) + \cos(4t) \leftrightarrow \dfrac2{s^2+4} + \dfrac{s}{s^2+16} = \boxed{\dfrac{s^3+2s^2+4s+32}{s^4+20s^2+64}}[/tex]